2017
DOI: 10.1371/journal.pntd.0005250
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Antigen B Protein Species Present in the Hydatid Cyst Fluid of Echinococcus canadensis G7 Genotype

Abstract: The larva of cestodes belonging to the Echinococcus granulosus sensu lato (s.l.) complex causes cystic echinococcosis (CE). It is a globally distributed zoonosis with significant economic and public health impact. The most immunogenic and specific Echinococcus-genus antigen for human CE diagnosis is antigen B (AgB), an abundant lipoprotein of the hydatid cyst fluid (HF). The AgB protein moiety (apolipoprotein) is encoded by five genes (AgB1-AgB5), which generate mature 8 kDa proteins (AgB8/1-AgB8/5). These gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 52 publications
(71 reference statements)
0
19
0
1
Order By: Relevance
“…On the other hand, as PLD treatment did not provoke a total reduction in hCRP‐binding activity, other EgAgB moieties would participate in CRP‐EgAgB interaction. EgAgB protein moieties seem not to be involved since rEgAgB8/1—the most abundant apolipoprotein in native EgAgB—as well as rEgAgB8/2 and rEgAgB8/3 were unable to compete with native EgAgB for CRP binding. Cholesterol, which is also present in native EgAgB, may play a role as it has been associated with CRP binding to LDL particles …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, as PLD treatment did not provoke a total reduction in hCRP‐binding activity, other EgAgB moieties would participate in CRP‐EgAgB interaction. EgAgB protein moieties seem not to be involved since rEgAgB8/1—the most abundant apolipoprotein in native EgAgB—as well as rEgAgB8/2 and rEgAgB8/3 were unable to compete with native EgAgB for CRP binding. Cholesterol, which is also present in native EgAgB, may play a role as it has been associated with CRP binding to LDL particles …”
Section: Discussionmentioning
confidence: 98%
“…Regarding EgAgB moieties involved in CRP recognition, PC is of foremost importance as the removal of the phosphocholine group of PC caused a significant reduction (60%) of hCRP binding to EgAgB. Given that PC is the most abundant phospholipid in EgAgB purified from different host species (bovine, porcine and human), CRP recognition of EgAgB might be a common event in natural CE infections. On the other hand, as PLD treatment did not provoke a total reduction in hCRP‐binding activity, other EgAgB moieties would participate in CRP‐EgAgB interaction.…”
Section: Discussionmentioning
confidence: 99%
“…However, the detection and the abundance of AgB8/2 to 5 in HF is rather variable [8,9,14,37]. Also, the AgB subunits representation in HF vary among different Echinococcus species [14,38]. multilocularis [13,37,39].…”
Section: Papilin Belongs To the Adamts (A Disintegrin-like And Metallmentioning
confidence: 99%
“…A recent study with AgB particles obtained from fertile HF of swine origin, infected by Echinococcus canadensis , a closely related specie, also found AgB8/1 as the most represented subunit. Additionally, the authors found AgB8/4, AgB8/3 and AgB8/5, while AgB8/2 was not detected [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that delipidated AgB is able to bind hydrophobic compounds in vitro [ 14 ]. The lipid moiety associated with AgB represent 40–50% of the total particle mass and is constituted by different lipid classes, from hydrophobic lipids, like sterol esters and triacylglycerides, to a variety of phospholipids [ 9 , 13 ]. Moreover, delipidated recombinant AgB8/2 and AgB8/3 subunits were capable of transferring fatty acids analogues to artificial phospholipid membranes [ 15 ].…”
Section: Introductionmentioning
confidence: 99%